The double-edged role of firm environmental behaviour in the creation of product innovation in Central and Eastern European countries. (10th January 2022) - Prokop, Viktor; Gerstlberger, Wolfgang; Zapletal, David; Striteska, Michaela Kotkova
Abstract: Prior research has primarily focused on how firm environmental behaviour affects firm performance and eco-innovation, whereas the mechanisms involved in this relationship were treated as a black box. This study steps back to focus on the reverse relationship between firms' environmental behaviour and 'general' product innovations in Central and Eastern European countries, which generally face low levels of consciousness about environmental issues. Specifically, we focus on the Czech Republic, Estonia, Latvia, Lithuania, Poland, and Slovakia. The results show that firms' environmental behaviour acts in two ways and brings significant differences between the considered countries. Surprisingly, the monitoring of energy consumption helps increase firms' chance to create more product innovation in lagging countries, such as Slovakia and Poland, than in leading innovation countries, such as the Czech Republic, Lithuania, and Latvia. Moreover, adopting measures of water management proved to be a significant determinant of product innovation despite the fact that it is not often used. The presented article contributes to the current state of knowledge in the areas of (i) determinants of (eco-) innovation; (ii) ongoing discussion about the Porter hypothesis; and (iii) catching-up literature dealing with (eco-) innovation in Central and Eastern European countries. In the final section, practical contributions in the form of implications are presented. Highlights: Reverse relationship between firms' environmental behaviour and product innovation. Energy consumption monitoring differently affects the product innovations creation. High attention of machinery and equipment upgrades' measures. Significant effects of water management measures on the product innovation. Differences between neighbouring countries (e.g., Slovakia and the Czech Republic).